The development and validation of mood scales suitable for use with stroke patients with aphasia - Barrows, Paul David (2016)
About a third of stroke survivors have some degree of depression. Depression has a significant impact on recovery after stroke, and identification is important so it can be treated. A common symptom of stroke is aphasia, where comprehension or expression of language is significantly impaired. Communication problems following stroke have been shown to be a major predictor of depression after stroke, yet these problems often make assessment of mood using conventional, language-based measures difficult or impossible.